Attitudes of youth towards corruption in Kuwaiti society - Al-Kindari, Yaqoub; Al-Kindari, Mohammad (Jordan Journal of Social Sciences, 2021)
The present study aims to identify the attitudes of Kuwaiti youth towards corruption's proportion, forms, reasons, and the responsibility of social institutions. Methods: Descriptive method has been used. The sample of the study included (322) respondents (17-32 years). Ministry of Youth definition of youth in Kuwait has been used. The questionnaire was the major tool of this study. It included two parts: respondents' primary information and four scales measuring corruption proportion, forms, reasons and social institutions responsibility. SPSS was used for data entry and analysis. Descriptive and inferential statistics were used: One -Sample and Independent t-test, Pearson correlation, and Alpha-Cronbach. Results: The study revealed that young Kuwaitis see that the proportion of the corruption is high. Social, financial, administrative, and behavioral forms aspects are responsible of corruption in Kuwait. Also, there is an inappropriate role for the institutions to avoid the spread of the corruption. Data found that there are significant differences related to the portion of corruption and its forms, reasons, and the role of institutions in fighting it and age variables (young youth and older young) and gender. The study revealed that there is also statistically significant relationship between the portion of corruption and its forms, reasons, and the role of institutions in fighting it. Conclusion: Corruption significantly affects the value system of the youth segment, and there is a tendency for social acceptance of corruption as phenomena in the Kuwait Society. This is greatly affects the future and stability of society. The study suggests that it is important to apply what is called the principles of good governance. Otherwise, corruption will become as a phenomena in Kuwait.